The function of the educational computer in the acquisition of art education students' skills in implementing the rules of perspective (Journal of the College of Basic Education, 2022)
Educational technologies in general, and the educational computer in particular, are considered an essential pillar of the educational-learning process and an integral part of the comprehensive educational system. And communication and its developments, in order to achieve its goals in accordance with the educational / learning system